Special aspects of the measurement of the internal geometric parameters of the channel parts of small size - S. V. Zakhorevich; I. V. Borisovets; I. P. Lazebnikova (Литьë и металлургия, 2019)
Technical measurements of linear-angular sizes of parts and products are the most common in mechanical engineering and make up to 95% of the measurements of all controlled sizes. Measuring control is an integral part of each operation of technological processes of production, assembly, testing of products. The complex method of measuring the external and internal geometric characteristics of a carbide die, given in the article, allows to measure the geometric parameters of small-size parts and to give a final assessment of the product for compliance with the requirements of the project technical documentation.